Big Stadium, Small City: A Catalyst for Turbulence and Governance Reforms. Issue 3 (3rd July 2019) - Sam, Michael P.; Scherer, Jay
ABSTRACT: New sport stadia are always contentious projects but in small cities, the stakes may be proportionally higher. This study analyses the turbulence generated by a stadium's approval and financing in Dunedin, New Zealand (2004-2017).It analyses: 1) the city's deferment of advice and fundraising to a charitable trust, 2) the financing apparatus that used council-owned companies (COCs) to obfuscate costs, and 3) the resultant consequences including legal proceedings, COC reforms and company failures. It is suggested that the porousness of governance arrangements invited scrutiny of the links between the city and its COCs, and by extension induced a temporary halt to the softening public-private boundary.